Prática profissional integrada ao ensino médio integrado do IFFar: balanços e perspectivas - Minuzzi, Evelize Dorneles (2022)
Integrated high school education seeks to overcome educational du ality and curricular fragmentation, by merging professional and introductory education in a single course, offered by the Institutos Federais de Educação, Ciência e Tecnologia (IFs), and materialized by the integrated curriculum. However, its implementatio n in practice has , not been an easy task, due to the crossing of political, legal, institutional, organizational and pedagogical factors, which has led to the emergence of methodological alternatives, such as the Prática Profissional Integrada (PPI), approv ed by the Instituto Federal Farroupilha (IFFar), since 2013, as part of the curriculum organization of all its integrated technical courses. However, despite being an institutional practice, it has not yet become, uniformly, institutionalized in the daily routine of the classroom. Thus, the objective of this study was to analyze the necessary and sufficient conditions for the practical development of Prática Profissional Integrada as an institutionalized methodological possibility within the IFFar, having t he São Vicente do Sul Campus as the locus of the research, and its teachers and students as subjects. In its methodological path, the principles of qualitative research were adopted, of the researchaction type, with dialectical historical materialism as a n investigative reference. Initially, a diagnosis was made through the study of institutional documents and the application of semistructured interviews with a group of five teachers, in which the data were analyzed based on content analysis, resulting in manuscript I. Subsequently, the cycles of planning, a , the ction and evaluation were developed, in which the data collection of the first two cycles was supported by participant observation and field diary, while the evaluation cycle was guided by the Likert sc ale questionnaire, with the return of 32 teachers and 204 students from the four integrated technical courses, being analyzed with the support of descriptive statistics and content analysis, composing the manuscript II. The results point to an expansion of the conceptualization when the integration of subjects with the world of work emerges, but, at the same tim to a superficiality and a distancing, when not dealing with the principles of integrated high school education, and to an operationalization mark ed by difficulties related to the disintegration of the administrative wh outweighsdidacticpedagogical organization and to the presence of disciplinarity, eigh the advances. In such a way, it is concluded that for the PPI to become an institutionalized peda gogical practice in the everyday classroom needs to integrate and pursue the epistemological, methodolo , logical, o , gical and pedagogical clues in a rdered and coherent way, thus permeating its formative, structural, organizational, didactic and pedagogical n ature.